2021
DOI: 10.3389/fpls.2021.774098
|View full text |Cite
|
Sign up to set email alerts
|

An F-Actin Mega-Cable Is Associated With the Migration of the Sperm Nucleus During the Fertilization of the Polarity-Inverted Central Cell of Agave inaequidens

Abstract: Asparagaceae’s large embryo sacs display a central cell nucleus polarized toward the chalaza, which means the sperm nucleus that fuses with it during double fertilization migrates an atypical long distance before karyogamy. Because of the size and inverted polarity of the central cell in Asparagaceae, we hypothesize that the second fertilization process is supported by an F-actin machinery different from the short-range F-actin structures observed in Arabidopsis and other plant models. Here, we analyzed the F-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…For example, SPA17, IQCG, ACTB, 5-HT , and the HOX gene family. The IQCG is also involved in spermatogenesis and is a key regulator of cilia/flagellar motility and is associated with sperm motility ( Harris et al, 2014 ; Gonzalez-Gutierrez et al, 2021 ). Additionally, the studies have also reported that β -actin is potentially involved in sperm maturation, sperm excretion, and the ability to maintain sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SPA17, IQCG, ACTB, 5-HT , and the HOX gene family. The IQCG is also involved in spermatogenesis and is a key regulator of cilia/flagellar motility and is associated with sperm motility ( Harris et al, 2014 ; Gonzalez-Gutierrez et al, 2021 ). Additionally, the studies have also reported that β -actin is potentially involved in sperm maturation, sperm excretion, and the ability to maintain sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…In both plants and animals, cytoskeletal structures such as actin filaments (F-actin) and microtubules (MTs) regulate many fundamental cellular processes [18][19][20][21][22][23][24][25] , including those in plant reproduction such as pollen tube growth and guidance, sperm nuclear migration, and asymmetric division of the zygote [18][19][20][26][27][28] . Immunostaining studies of coenocytic endosperm at interphase revealed a nucleus-based radial MT (aster-shaped) system that organizes cytoplasm into nuclearcytoplasmic domains [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%